Analysis of Consumer Satisfaction Level with the Quality of Non-Prescribed Medicine Services in Malang City Pharmacies - Hakim, Abdul; Suryadinata, Arief; Al Halim, Syarif (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 4 (2024): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v4i0.3311, 2025)
Pharmacies is defined as a pharmaceutical service facility where pharmacy practices are carried out by pharmacist. In carrying out the pharmaceutical work at pharmaceutical service facilities, pharmacists must apply pharmaceutical services standard. The consumer satisfaction level is a scoring or evaluation after behaving a service, that a chosen service at least has fulfilled or exceeding the expectations. The quality of services is an expected level of excellence and control over the level of excellence to meet consumer or consumer desires. The research design that is used is descriptive quantitative research. According to the research rule, the researcher obtains a result that shows the consumer satisfaction levels on the quality of the service on every dimensions through every dimensions is in the intermediate level (-0.81 until 0.80), with the total average gap on (-0.29). However, according to the total percentage score of the consumer satisfaction level against the service quality dimension is 83.24%, it can be concluded that the consumers are extremely satisfied (80-100%) against the services that are given by the pharmacies around Lowokwaru District Malang City.